ONE OF THE WAYS TO RISE THE EFFICIENCY OF THE KISHINEV TOWN HEAT AND POWER STATIONS - Maximuk E.P. (Problems of the Regional Energetics)
Methods to rise the efficiency of fuel using at town heat and power stations are discussed in detail. It is shown that application of hot water/exhaust absorption chillers allow to use heat energy surplus especially in warm season. As the results, the consumption of heat energy from the power stations is more constant during the year, the efficiency of fuel using is higher, and economics is better. Different technological schemes are discussed in detail.